A new interactive approach for solving fully fuzzy mixed integer linear programming - Khalili, Goudarzi; Nasseri, Seyed; Taghi-Nezhad, Nemat (Yugoslav Journal of Operations Research, 2020)
In this paper, a novel method to solve Fully Fuzzy Mixed Integer Linear Programming (FFMILP) problems is presented. Our method is based on the definition of membership function and a fuzzy interactive technique for solving the classical multiobjective programming. It is worthwhile to note that this is the first time that the fully fuzzy mixed integer linear programming problem is discussed and a solving method is presented. To illustrate the steps of the proposed method, some numerical examples are solved and the results are compared with other methods in the literature. Computational results present the application of the method. nema